Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.26907/mrsej-19101
|View full text |Cite
|
Sign up to set email alerts
|

Probing the surface of synthetic opals with the vanadyl containing crude oil by using EPR and ENDOR techniques

Abstract: Porous silica materials offer wide range of possibilities for enhancement of the productivity of oil reservoirs. However the mechanism of adsorption of polar components of crude oil on silica surface is poorly understood that hinders technological improvement of supports and oil extraction. We have synthesized opal films with the silica microspheres size of about 360 ± 20 nm, specific surface area of 5.2 m 2 × g −1 and pore size of 230 nm. We have fractionated and characterized oil and oil asphaltenes from hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…62 In addition, because we use clean NaCl(2 ML)/Ag(111) as a substrate, we can exclude the alteration of the petroporphyrin properties by proton-containing groups from the surface, as was found in previous work using amorphous SiO 2 surfaces. 63 We found that many of the molecules were inadvertently manipulated by the SPM tip during scanning, indicating the frequent presence of bulky and nonplanar side groups attached to the porphyrin core. The contrast in CO-AFM depends upon the repulsive forces as a result of Pauli’s exclusion principle, which exhibits a steep dependence upon the tip–sample distance.…”
Section: Resultsmentioning
confidence: 87%
“…62 In addition, because we use clean NaCl(2 ML)/Ag(111) as a substrate, we can exclude the alteration of the petroporphyrin properties by proton-containing groups from the surface, as was found in previous work using amorphous SiO 2 surfaces. 63 We found that many of the molecules were inadvertently manipulated by the SPM tip during scanning, indicating the frequent presence of bulky and nonplanar side groups attached to the porphyrin core. The contrast in CO-AFM depends upon the repulsive forces as a result of Pauli’s exclusion principle, which exhibits a steep dependence upon the tip–sample distance.…”
Section: Resultsmentioning
confidence: 87%
“…For example, NV fluorescent centers could be studied by optically detected magnetic resonance; further radiation damage centers or impurity may be created inside the diamond to introduce additional paramagnetic markers into the structure of nanoparticle. From the other hand, the presented results can be used for the investigation of adsorption of magnetic nuclei-containing substances that may be important to study supramolecular structures of oil asphaltenes and reaction of polymerization in the conditions of spatial/quantum confinement for using ND as catalysts …”
Section: Discussionmentioning
confidence: 99%
“…However, some organic radicals are long-lived, even shelf-stable, and commercially available, such as (2,2,6,6-tetramethylpiperidin-1-yl)­oxidanyl (TEMPO) and α,γ-bisdiphenylene-β-phenylallyl (BDPA). The presence of radical species in petroleum has been known since their detection using electron spin (or paramagnetic) resonance (ESR or EPR) in the late 1950s and remains a subject of active research today. They are carbon-centered free radicals based on the g value of 2.0034 ± 0.0004, indicating that a free electron is delocalized in a π system ( g is a spectroscopic splitting factor dependent upon the orbital, and the electronic environment of the electron, g e , is 2.0023 for the free electron). This is easily distinguished from paramagnetic metals, such as the septet peaks, as a result of vanadyl (VO 2+ ) petroporphyrins. , The presence of organic radicals in petroleum is unquestionable, but the featureless single EPR signal does not readily reveal information about their structures. , Much of the structural information that can be provided by EPR on individual radical species is lost, apparently as a result of overlapping signals from a mixture of diverse radicals.…”
Section: New Hypothesis For Asphaltene Aggregation Via Pancake Bondin...mentioning
confidence: 99%